2017
DOI: 10.1063/1.4994590
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a mode-2 internal solitary wave with narrow isolated topography

Abstract: Numerical and experimental studies of the transit of a mode-2 internal solitary wave over an isolated ridge are presented. All studies used a quasi-two-layer fluid with a pycnocline centred at the mid-depth. The wave amplitude and total fluid depth were both varied, while the topography remained fixed. The strength of the interaction between the internal solitary waves and the hill was found to be characterized by three regimes: weak, moderate, and strong interactions. The weak interaction exhibited negligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The combined numerical and laboratory investigation undertaken in the Deepwell et al (2017) study provided, for the first time, clear indications of flow separation and vortex formation on the upward boundary slope of the topography as a characteristic property of shoaling mode-2 waves of large and moderate amplitude. The numerical modelling study by Cheng et al (2017) considered the distortion caused to mode-2 waves by passage over a combined slope-shelf topography placed in a channel having the same dimensions and gate release wave generation mechanism in the experiments described by Carr et al (2015); Deepwell et al (2017) and the present investigation. Test runs conducted by Cheng et al (2017) to replicate the laboratory study by Carr et al (2015) for constant depth conditions showed excellent agreement between numerical simulations and laboratory data.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The combined numerical and laboratory investigation undertaken in the Deepwell et al (2017) study provided, for the first time, clear indications of flow separation and vortex formation on the upward boundary slope of the topography as a characteristic property of shoaling mode-2 waves of large and moderate amplitude. The numerical modelling study by Cheng et al (2017) considered the distortion caused to mode-2 waves by passage over a combined slope-shelf topography placed in a channel having the same dimensions and gate release wave generation mechanism in the experiments described by Carr et al (2015); Deepwell et al (2017) and the present investigation. Test runs conducted by Cheng et al (2017) to replicate the laboratory study by Carr et al (2015) for constant depth conditions showed excellent agreement between numerical simulations and laboratory data.…”
Section: Introductionmentioning
confidence: 86%
“…In practice, such smoothing does not modify the ISWs generated, but does decrease the amount of turbulence near the release location. The code has been found to do an excellent job in reproducing experimental results, for example in propagation of mode-2 ISWs over isolated topography (Deepwell et al 2017).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in quasi-mode-2 models such appearance was mostly found in shallower waters of < 200 m under the ridge-top crest and only at near-buoyancy frequencies, during ebb-flow. Most observations and modeling show high-frequency solitary waves in quasi-mode-2 that may occur every tidal period (e.g., Ramp et al, 2012;Deepwell et al, 2017;Xie et al, 2017). To our knowledge only once actual quasi-mode-2 internal tides were suggested to exist (Farmer and Smith, 1980).…”
Section: Internal Wave Observations Off Saba Bankmentioning
confidence: 82%